2017
DOI: 10.1007/s12161-017-1118-5
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Method Based on Natural Deep Eutectic Solvents for Extraction of Flavonoids from Food Samples

Abstract: Natural deep eutectic solvents (NADES) are promising green solvents for the extraction of compounds from natural products. This is the first study to use a sample preparation method based on NADES for the extraction of flavonoids (rutin, hesperidin, neohesperidin, naringenin, naringin, quercetin, hesperetin, and chrysin) from fruits, vegetables, and spices. In total, 17 types of NADES based on choline chloride, acetylcholine chloride, choline tartrate, betaine, and carnitine with different compositions were ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(86 citation statements)
references
References 38 publications
1
66
0
3
Order By: Relevance
“…The NADES solvent used was a betaine base with combinations of four components; betaine: urea (1:1) [9,12,14], betaine: lactic acid (1:1) [12,15], and betaine: malic acid (1:1) [9,12]. There are three methods of preparation of NADES solvents, comprising heating and stirring methods, evaporation methods, and freeze-drying methods [16].…”
Section: Preparation Of Nadesmentioning
confidence: 99%
“…The NADES solvent used was a betaine base with combinations of four components; betaine: urea (1:1) [9,12,14], betaine: lactic acid (1:1) [12,15], and betaine: malic acid (1:1) [9,12]. There are three methods of preparation of NADES solvents, comprising heating and stirring methods, evaporation methods, and freeze-drying methods [16].…”
Section: Preparation Of Nadesmentioning
confidence: 99%
“…The work of Brahmachari () describes more than 160 naturally occurring flavanones that belong to 36 plant families. Flavanones are present in vegetables, that is, tomato, potato (Durazzo et al, ), spices, that is, rosemary and peppermint (Bajkacz & Adamek, ), and particularly in fruits, that is, lemon, orange, strawberry, raspberry, and plum (W. Cao et al, ; Pavlović et al, ; Sablani et al, ). Khan, Huma, and Dangles () showed that hesperetin (Figure a) and its derivatives are characteristic flavanones of sweet orange, tangelo, lemon, and lime, whereas naringenin (Figure b) and its derivatives are peculiar of grapefruit and sour orange.…”
Section: Phenolic Compoundsmentioning
confidence: 99%
“…The increased DPPH activity can be attributed to the higher amount of antioxidants in the extracts. Bajkacz et al [44] stated that the increase in water content (more than 10%) in DES increased the flavonoid recovery from food samples. According to them, the best yields were obtained with 30% water content, while the further increase up to 75% decreased the flavonoid content.…”
Section: Response Surface Analysis and Process Optimizationmentioning
confidence: 99%